2002
DOI: 10.1080/mmy.40.4.359.375
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Protective Host Defenses against oral and vaginal Candidiasis

Abstract: Oral and vaginal candidiasis are the two most common forms of opportunistic fungal infections. However, the prevalence of each can be quite variable depending on the immune status of the host. While vulvovaginal candidiasis (VVC) is equally common in immunocompetent and immunocompromised women, oropharyngeal candidiasis (OPC) is infrequent except under immunocompromised states. Candida albicans, the causative agent in the majority of cases, is a commensal of the gastrointestinal and lower female reproductive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 154 publications
(119 reference statements)
1
13
0
Order By: Relevance
“…Previously, RVVC was thought to be attributable to defects in systemic and local cell-mediated immunity, similarly to other forms of candidiasis, in which protection against infection is T-cell dependent (reviewed in reference 4). However, numerous studies using a mouse model and cross-sectional clinical studies have shown that local or systemic adaptive immunity and associated cytokine/chemokines have no role in protection against vaginitis (510).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, RVVC was thought to be attributable to defects in systemic and local cell-mediated immunity, similarly to other forms of candidiasis, in which protection against infection is T-cell dependent (reviewed in reference 4). However, numerous studies using a mouse model and cross-sectional clinical studies have shown that local or systemic adaptive immunity and associated cytokine/chemokines have no role in protection against vaginitis (510).…”
Section: Introductionmentioning
confidence: 99%
“…Topics of particular interest are the organism's capacity to shift into several different phenotypic states, some with distinct roles in infection, and its recently discovered capacity to mate, providing at least part of a sexual cycle, although population genetic studies indicate that it is still largely a clonal diploid population. Other special adaptations for infection include a battery of externally displayed proteins and secreted digestive enzymes; complex interactions with the host immune system normally keep C. albicans at bay as a minor part of the mucosal flora [1,4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…It also causes systemic infections in immunocompromised individuals or patients undergoing long-term treatment with antibiotics (1) (2) . Side effects of the present treatment regimens for C. albicans and the advent of multidrug resistance (MDR) are problems affecting effi cient therapy against infections caused by C. albicans (3) (4).…”
Section: Introductionmentioning
confidence: 99%